Corporate governance, market discipline, and productivity growth - Jens Köke (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2001)
Using a large panel of German manufacturing firms over the years 1986?1996, this study examines the impact of corporate governance and market discipline on productivity growth. We find that firms under concentrated ownership tend to show significantly higher productivity growth. Financial pressure from creditors influences productivity growth positively, particularly for firms in financial distress. Regarding market discipline, productivity grows faster when competition on product markets is intense, but only when owner concentration is high. We do not find evidence that the type of the owner, ownership complexity, or the size of the supervisory board is significantly related to productivity growth.
Keywords: G32; D43; D24; 330; competition; corporate governance; productivity; ownership structure; Produktivität; Verarbeitendes Gewerbe; Corporate Governance; Eigentümerstruktur; Wettbewerb; Schätzung; Deutschland